Pengaruh Kompetensi Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Sekretariat Kabupaten Buru - Iriyani Yendra; Petronela Sahetapy; Aminah Bahasoan (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the effect of competence and work motivation on employee performance at the Secretariat of Buru Regency. Employee performance is a crucial factor in supporting the effectiveness of local government administration, requiring proper human resource management. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of the Buru Regency Secretariat as research respondents. Data analysis was conducted using multiple linear regression to examine the partial and simultaneous effects of competence and work motivation on employee performance. The findings indicate that competence has a strong influence on employee performance, as adequate knowledge, skills, and work attitudes enable employees to perform their duties more effectively. In addition, work motivation contributes to improved performance by encouraging commitment and work enthusiasm. Overall, competence and work motivation complement each other in enhancing employee performance. Therefore, strengthening employee competence and increasing work motivation should be prioritized in human resource management at the Secretariat of Buru Regency to improve organizational performance.